Significance of the detection of beta-galactosidase and of beta-xylosidase in the taxonomic study of the genus Haemophilus. Issue 10 (October 1979) - Hansen, W; Schoutens, E; Yourassowsky, E
Abstract : A total of 314 strains of Haemophilus, isolated from clinical samples, were studied for the production of beta-galactosidase and beta-xylosidase. None of the H. influenzae strains studied (9 beta-lactamase positive strains and 129 beta-lactamase negative strains) possessed these enzymes. Both enzymes were almost constantly observed among strains of H. paraphrophilus (10 strains studied) and of H. paraphrohaemolyticus (9 strains studied). Among the other species (H. parainfluenzae, 55 strains; H. haemolyticus, 5 strains; H. parahaemolyticus, 97 strains), beta-galactosidase was present in about 30% of the strains studied whereas beta-xylosidase was detected occasionally (3% of the strains studied). Detection of these two enzymes could be a valuable test for the taxonomic study of the genus Haemophilus. However, the type of substrate used for the detection of beta-xylosidase is important: use of the para-nitro-phenyl-beta-xylopyranoside yielded more positive results than the use of its ortho-isomer.